071. Pantaloon Hernia with Bladder Herniation: A Case Report And Review Of Literature - Sulistyo, Heru; Rosyada, Amrina (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p071, 2024)
Background : Pantaloon hernias are a rare mix of direct and indirect inguinal hernias on the same side, making them clinically challenging. Bladder herniation, which can occur with pantaloon hernias, adds specific diagnostic and treatment challenges. Inguinal hernias account for about 75% of all abdominal wall hernias and mostly affect men. Case :  A 57-year-old man came to Saiful Anwar Hospital with a left inguinal lump that had been present for six days. He also experienced abdominal swelling, pain, nausea, and vomiting. The lump had become irreducible for the last two days. A physical exam showed a 13x7 cm mass in the left inguinal area. The patient had signs of an inguinal hernia and reported urinary issues, including a feeling of incomplete emptying and urination. Surgery was done on January 13, 2024, using an open technique. During the procedure, the hernia sac had fluid, trapped ileum, and omentum. A part of the bladder was also found protruding through the Inguinal Triangle of Hasselbach, causing a 1x1 cm defect. The hernia sac was repaired with a 10x15 cm mesh. Conclusion: This case highlights the rarity of pantaloon hernias and emphasizes the importance of prompt diagnosis and intervention. Continued research is essential for advancing clinical outcomes and understanding the complexities associated with this condition